Validity and reliability of a robotic sprint resistance device - Rakovic, E.; Paulsen, G.; Helland, C.; Haugen, T.; Eriksrud, O. (The Journal of Strength and Conditioning Research, 2020)
An increasing numberof sprint-related studies have employed robotic devices to provide resistance while sprinting.The aim of this study was to establish within-session reliability and criterion validity of sprint times obtained from a robotic resistance device. Seventeen elite female handball players (22.9?3.0y; 176.5?6.5cm; 72.7?5.5kg; training volume 9.3?0.7 hrsper week) performed two 30-m sprints under three different resistance loading conditions (50, 80 and 110 N).Sprinttimes (t0-5m, t5-10m, t10-15m, t15-20m, t20-30mand t0-30m) were assessed simultaneously by a 1080 Sprint robotic resistance device and a post-processing timing system.The results showed that 1080 Sprint timing was equivalent to the post-processing timing system within the limits of precision(?0.01 s). Asystematic bias of ~ 0.34 ± 0.01 s was observed for t0-5mcaused by differentathlete location and velocity at triggering pointbetween the systems.Coefficient of variation was ~ 2% for t0-5 and ~ 1% for the other time intervals, while standard error of measurement ranged from 0.01 to 0.05s, depending on distance and phase of sprint. Intraclass correlationranged from 0.86to 0.95.In conclusion, the present study shows that the 1080 Sprint is valid and reliable for sprint performance monitoring purposes.